Saúde do homem no município de Maringá-PR : comportamentos, necessidades e utilização dos serviços de saúde - Arruda, Guilherme Oliveira de (2013)
The main purpose of the present study, conducted in the city of Maringá, state of Paraná, Brazil, was to analyze behaviors, needs and use of health services among adult men. This research is constituted of two methodological approaches: one quantitative, cross-sectional and population-based (household survey), counting with the participation of 421 men living in the urban area of the city, aged between 20 and 59 years old, and another one qualitative, descriptive and exploratory, conducted with 10 men. Quantitative data was collected between January and July 2013, through structured instrument, and analyzed through descriptive and inferential statistics (chi-square test and logistic regression). Qualitative data was collected between September and November 2013 through semi-structured interviews and subjected to Content Analysis, a thematic modality. The results show that men with higher income and a health plan often reported abusive alcohol consumption, and smoking habit presented association with not having a religion and lower level of educational attainment. The age group from 30 to 39 years old and the job were linked to insufficient physical activity, and the economic class C to inadequate diet. Absence of a partner and the economic class D were associated with inadequate immunization status and neglect of preventive health exams. Absence of leisure activities was predominant among men over 50 years old and among those of the economic class C. The prevalence of use of health services in the last three months was of 42.8%, and associated variables were "occupational status", "health plan", "management type of the service", "hospitalization in the last year" and "reported morbidity". Regarding use of public health services, a prevalence of 56.3% was observed, being higher among men with elementary education, without health plan and without a partner, who had a greater contact with nurses and other professionals, searched for the services often due to illness, reported morbidity, were faced with difficulties regarding assistance, classified the services as regular, and judged attention and promptness as the most important aspects in healthcare. In the quantitative analysis of health needs indicators, age group and occupational status were associated with self-perception of regular/poor health and reported morbidity. In the qualitative analysis, it was possible to understand that health needs include good diet, practice of physical activity, performance of periodic exams, exercise of religiosity/spirituality, having a job and maintaining good interpersonal relationships, besides economic status, place of residence and access to health services. It was observed that men look for hospitals mainly to meet their needs of clinical nature, and that attention to these needs should involve political intersectorial articulation and respectful attitude from health professionals. Male perceptions are crossed by questions of gender, and the way men think about their health is influenced by women, whether their spouses or mothers. The findings of the present study reinforce that socioeconomic and demographic variables are important, because they were associated with health-related behaviors. The prevalence of use of health services were similar to that of other studies, and other variables, besides socioeconomic and demographic, should be focused on prevention actions for men's health, such as recent hospitalization, presence of morbidity and even the management type of the health service. As for the use of public health services, assistance to men requires attention, promptness and improvements. Health needs could be analyzed under different approaches, which allows nurses to expand their view over the needs of men, identifying variables that can indicate them, associated factors and male perceptions on them.